PEertunjukan Mahakarya Legenda Goa Kreo: Sebelum, Saat dan Sesudah Pertunjukan dalam Manajemen Tirang Community di Kota Semarang - Saguh Ridhatul Hidayat; Mohammad Hasan Bisri (Program Studi Pendidikan Tari FBS UNJ, 2023)
Tirang Communtiy is a group consisting of dance, music and drama activists. The existence of Tirang Community is able to invite young people to join in order to love traditional culture and arts and to package arts so that they are easily accepted by the community. This is the reason for researchers to study the performance of the Kreo Goa Legendary Masterpiece: Before, When and After Performances in Tirang Community Management in Semarang City. The research objective is to analyze the form of the Goa Kreo Legend Masterpiece performance, and analyze the Tirang Community management in the production of the Goa Kreo Legend Masterpiece. Researchers used a phenomenological approach and qualitative methods in preparing research results. The results showed that the form of the Goa Kreo Legend Masterpiece show consisted of pre-show and the core of the show. The supporting elements of the Goa Kreo Legend Masterpiece show consist of performers, movements, accompaniment, fashion, makeup, lighting, settings, themes, plot, floor patterns, places, expressions, properties, and spectators. Tirang Community carries out managerial activities by including management functions and management elements. Tirang Community management factors consist of organizational management, production activity management and show management